Power supervision of an autonomous photovoltaic/wind turbine/battery system with MPPT using adaptative fuzzy logic controller - Djamila Rekioua; Samia Bensmail; Chafiaa Serir; Toufik Rekioua (International Journal of Applied Power Engineering (IJAPE), 2023)
In this work a power supervision of an autonomous photovoltaic/wind turbine/batteries system is presented. Measurements of weather conditions during different has been made. Due to the instantaneous changing of solar irradiance, temperature and wind speeds, maximum power point tracking (MPPT) is integrated. Due to its ease of use, the perturb and observe (P&O) algorithm is the most preferred, but has a great disadvantage of oscillations at steady state. The adaptative fuzzy logic controller (AFLC) method is also widely used for its advantages of fast response with better performance than the classical FLC and P&O strategies. An accurate sizing methodology was applied in the proposed sizing approach to calculate the PV and wind turbine generators number. To manage the various powers, supervision method is simple, easy realization and not heavy computation. A simulation study under MATLAB/Simulink has been made. The different results are given and analyzed.